USM AMBIENCE AND AMENITIES KEY IN NURTURING TALENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 25 March 2016 Renowned throughout the country for its broadcasting programme being of repute and having experience in the industry, the Universiti Sains Malaysia (USM) School of Communication has assisted in nurturing the talents of its students to achieve their highest potential.